1997
DOI: 10.1016/s0370-2693(97)00143-3
|View full text |Cite
|
Sign up to set email alerts
|

Same-sign dileptons as a signature for heavy Majorana neutrinos in hadron-hadron collisions

Abstract: We discuss the possibility of same-sign dileptons as a signature for Majorana neutrinos. The production mechanism is given by a single heavy neutrino production and decay pp −→ l ± N X −→ l ± l ± X ′ . Cross section and distributions are presented for the LHC energies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…As a result, searches for anomalous production of same-sign dileptons can be very sensitive to new physics contributions. These include supersymmetry (SUSY) [1][2][3], universal extra dimensions [4], pair production of T 5/3 particles (fermionic partners of the top quark) [5], heavy Majorana neutrinos [6], and same-sign top-pair production [7,8]. More specifically, the signature of same-sign dileptons accompanied by bottom quarks can arise from SUSY processes where third-generation quark superpartners are lighter than other squarks [9][10][11][12][13], resulting in an abundance of top and bottom quarks produced in cascade decays.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, searches for anomalous production of same-sign dileptons can be very sensitive to new physics contributions. These include supersymmetry (SUSY) [1][2][3], universal extra dimensions [4], pair production of T 5/3 particles (fermionic partners of the top quark) [5], heavy Majorana neutrinos [6], and same-sign top-pair production [7,8]. More specifically, the signature of same-sign dileptons accompanied by bottom quarks can arise from SUSY processes where third-generation quark superpartners are lighter than other squarks [9][10][11][12][13], resulting in an abundance of top and bottom quarks produced in cascade decays.…”
Section: Introductionmentioning
confidence: 99%
“…The excluded regions from LEP are based on searches for sleptons and charginos [42][43][44][45][46]. Other final states, especially the all-hadronic [22], are better suited for this standard reference model, while the leptonic same-sign final state explored in this paper is more appropriate to constrain a wide variety of other new physics models [1][2][3][4][5][6][7]. As discussed in section 4, in a general supersymmetry context, one might expect gluino-gluino or gluino-squark production to lead to same-sign dilepton events via a decay chain involving a chargino.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…In particular, they have been proposed as signatures of supersymmetry (SUSY) [1][2][3], universal extra dimensions [4], pair production of T 5/3 (a fermionic partner of the top quark) [5], heavy Majorana neutrinos [6], and same-sign top-pair resonances as predicted in theories with warped extra dimensions [7]. In this paper we describe searches for new physics with same-sign isolated dileptons (ee, eµ, µµ, eτ , µτ , and τ τ ), missing transverse energy (E miss T ), and hadronic jets.…”
Section: Introductionmentioning
confidence: 99%
“…In the general mass matrix including Dirac and Majorana fields one imposes some internal symmetry that makes the matrix singular. Then the mixing parameter has an arbitrary value, bounded only by its phenomenological consequences.Recently we have investigated this possibility for a single heavy Majorana production in hadron-hadron colliders [8]. It was shown that this mechanism is more important than pair production and that like-sign dileptons can give a clear signature for this process, even after hadronization.…”
mentioning
confidence: 99%
“…Recently we have investigated this possibility for a single heavy Majorana production in hadron-hadron colliders [8]. It was shown that this mechanism is more important than pair production and that like-sign dileptons can give a clear signature for this process, even after hadronization.…”
mentioning
confidence: 99%